Survivin Small Molecules Inhibitors: Recent Advances and Challenges - Najah Albadari; Wei Li (Molecules, 2023)
Survivin, as a member of the inhibitor of apoptosis proteins (IAPs) family, acts as a suppressor of apoptosis and plays a central role in cell division. Survivin has been considered as an important cancer drug target because it is highly expressed in many types of human cancers, while it is effectively absent from terminally differentiated normal tissues. Moreover, survivin is involved in tumor cell resistance to chemotherapy and radiation. Preclinically, downregulation of survivin expression or function reduced tumor growth induced apoptosis and sensitized tumor cells to radiation and chemotherapy in different human tumor models. This review highlights the role of survivin in promoting cellular proliferation and inhibiting apoptosis and summarizes the recent advances in and challenges of developing small-molecule survivin inhibitors.